Stages of formation psychological contact during the interrogation - Баранчук, В. В. (Theory and practice of jurisprudence, 2016)
This article examines the problems which are concerned with features establishment psychological contact during the interrogation at a pretrial investigation. A great attention is devoted to theoretical problems of phases formation establishment psychological contact and features of overcome conflict situations during interrogation process.